Banks' marketing strategies towards the undergraduate market - Ang, May Pheng (2015)
This report presents findings to the following objectives: firstly, to understand the marketing strategies used by banks; secondly, to measure the undergraduates' awareness of these banking services; thirdly, to measure the profit potential of the undergraduate market and finally, to determine the most influential factors that influence the undergraduates when utilising banking services. The research techniques used to collect the primary and secondary data included a combination of personal interviews, telephone interviews, mail questionnaires and literature review. The sampling variables were circumscribed to undergraduates from NTU and NUS, graduates within 5 years of graduation and full-licensed banks located in Singapore. Research findings conclude that the big 4 local banks: DBS, OCBC, OUB, UOB have the lion share in the undergraduate market with focused marketing efforts to develop customised strategies for this segment. Also, it was found that the DBS Tuition Fee Loan received most recognition from the undergraduates. Other significant findings include the rapid growth of the undergraduate population, the inertia of undergraduates and graduates in closing existing bank accounts as well as the graduates' need for more sophisticated banking products. Finally, it was found that convenience is the most significant factor influencing an undergraduate's operation of savings and current accounts, followed by better rates and financing purpose for the savings accounts and current accounts respectively.